2013
DOI: 10.3109/13693786.2012.686124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of dermatophytosis in Tehran, Iran, a clinical and microbial survey

Abstract: In the framework of a survey on dermatophytoses, 14,619 clinical specimens taken from outpatients with symptoms suggestive of tinea and referred to a Medical Mycology laboratory in Tehran, Iran, were analyzed by direct microscopy and culture. In total, 777 dermatophyte strains recovered in culture were randomly identified by a formerly established RFLP analysis method based on the rDNA ITS regions. For confirmation of species identification, 160 isolates representing the likely entire species spectrum were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 17 publications
10
79
4
Order By: Relevance
“…In the present study, T. interdigitale was the predominant pathogen in south of Iran, which corroborates recent findings reported from Iran investigating molecular epidemiology of dermatophytosis in Tehran [18] and north of Iran [17]. Interestingly, in our study, we found a significant increase in the frequency of A. benhamiae (5.38 %) significantly in a higher rate than previous studies in Iran [14,[17][18][19]24], reporting A. benhamiae as a rare dermatophyte.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, T. interdigitale was the predominant pathogen in south of Iran, which corroborates recent findings reported from Iran investigating molecular epidemiology of dermatophytosis in Tehran [18] and north of Iran [17]. Interestingly, in our study, we found a significant increase in the frequency of A. benhamiae (5.38 %) significantly in a higher rate than previous studies in Iran [14,[17][18][19]24], reporting A. benhamiae as a rare dermatophyte.…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm those of previous studies in Iran [13,24] and other regions of the world [32,33]. However, our finding is in contrast to others who reported tinea pedis [17,18], tinea capitis [15,32], and tinea cruris [19,20] as the predominant clinical observations in north and center of Iran.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…2). Trichophyton eriotrephon is known from three cases of human infection [26] that were probably transmitted from animal, based on the clinical picture and phylogenetic position of the species (Fig. 2).…”
Section: Phylogenetic Position Of Trichophyton Bullosummentioning
confidence: 99%